Construction of tetravalent bispecific Tandab (CD3/BCMA)-secreting human umbilical cord mesenchymal stem cells and its efficiency in the treatment of multiple myeloma - Mengshang Xiong; Chunfang Kong; Yang Lu; Jiaojun Liu; Weirong Ding; Tingting Zhang; Wei Zuo; Lixia Cao; Qiling Lu; Anna Li; Chaoyu Li; Liting Ding; et al. (Stem Cell Research & Therapy, 2025)
Abstract Background Highly efficient targeted therapy is urgently needed for multiple myeloma (MM). Mesenchymal stem cells (MSCs) are an attractive candidate of cell-based, targeted therapy due to their inherent tumor tropism. However, there is still no MSCs-based tandem diabody for treating MM. Methods Here, we designed a dual-target therapeutic system in which human umbilical cord MSCs (UCMSCs) were engineered to produce and deliver Tandab (CD3/BCMA), a tetravalent bispecific tandem diabody with two binding sites for CD3 and two for B-cell maturation antigen (BCMA). Western blot and flow cytometry were used to confirm the lentivirus-mediated construction of UCMSCs for diabody expression. The tropism of MSCs towards H929 cells in vitro was determined by migration assays, and the in vivo homing capacity of MSCs was analyzed by immunofluorescence staining. The activation and antitumor efficacy of human T cells mediated by MSCs secreting Tandab (CD3/BCMA) were evaluated in vitro. Finally, an MM xenograft NOD/SCID mouse model was established to investigate the therapeutic effect in vivo. Results We successfully constructed MSCs that can continuously secrete bioactive Tandab (CD3/BCMA), whereby lentiviral transduction did not affect the morphology, proliferation, and lineage differentiation potential of the MSCs. The tropism of MSC-Tandab for MM was verified both in vitro and in vivo. Furthermore, MSC-Tandab promoted the expansion and activation of primary human T cells and induced healthy donor T cells to selectively eliminate BCMA-positive cell lines and primary blasts from patients but not BCMA-negative cells. A similar ability was also observed in the patient-derived T cells. Finally, MSC-Tandab significantly alleviated the MM xenograft tumor burden in NOD/SCID mice without toxic side effects in vivo, whereby the cytokine levels (IFN-γ) in the peripheral blood (PB) were higher in the MSC-Tandab group, and the tumor infiltration of T cells was significantly enhanced. Conclusions These results suggest that UCMSCs releasing Tandab (CD3/BCMA) are a promising new tool for the treatment of MM, opening a new avenue for the development of cell-based therapy.